Plants vs. zombies. Snow thanks - Tobin, Paul, 1965-; Farris, Cat; Breckel, Heather; Dutro, Steve (Milwaukie, OR : Dark Horse Books, 2019)
"Dr. Zomboss invents a Cold Crystal, capable of freezing Neighborville, creating an eternal winter and burying both everyone in snow! With most of the zombie-battling plants chilled and immobile, Zomboss hopes to lead his troops on a mission to overrun the city. It's up to Nate, Patrice, Crazy Dave, and the plants to save Neighborville!"--Provided by publisher.
Based on the video game Plants vs. Zombies.
Keywords: Graphic novels; Zombies -- Fiction; Plants -- Fiction; Humorous stories; JUVENILE FICTION / Comics & Graphic Novels / Media Tie-In.; Graphic novels